To solve the equation \( 4x = 3(x + 5) - 15 \), we'll start by simplifying the right side of the equation.
-
Distribute the \( 3 \) on the right side: \[ 3(x + 5) = 3x + 15 \] So the equation becomes: \[ 4x = 3x + 15 - 15 \]
-
Simplify the right side: \[ 4x = 3x + 0 \] This simplifies further to: \[ 4x = 3x \]
-
Now, subtract \( 3x \) from both sides: \[ 4x - 3x = 0 \] This gives: \[ x = 0 \]
Since we obtained a specific value for \( x \) (i.e., \( x = 0 \)), the original equation has one solution.
Thus, the correct response is:
- The equation has one solution: \( x = 0 \).